Leadership training in improving the quality of Muhammadiyah Education in Makassar City - Nur Wahid; Sitti Rahmawati Arfah; Syukri Syukri; Indri Apriani Nur (Universitas Muhammadiyah Magelang, 2024)
This training aimed to assist schools in improving the quality of education through the development of strategic planning. The methodology employed in this activity was carried out in three stages: 1) preparation through socialization of the activity to the community; 2) implementation through training; and 3) evaluation conducted by distributing pre-test and post-test questionnaires to measure the knowledge and skills of the partners. The results of this community service indicated the effectiveness of the training with an increase in partners' knowledge and skills scores on the post-test (96.71%) compared to the pre-test (88.56%). This demonstrates a significant difference in the level of knowledge and skills after receiving the leadership training.